Formulation and evaluation of indomethacin biomicroparticles - Sudeep Gupta; Pawan Gaur; Kulwant Soam; Ruchi Suyal; Vinod Rana; Prashant Dabral (Wolters Kluwer Medknow Publications, 2012)
Indomethacin microparticles prepared by extraction of bio polymer from arachis hypogen. in vitro drug release study was carried out through egg shell membrane for 3 hrs and analyzed sample by UV spectroscopy at 320 nm. A novel bio membrane from arachis hypogen was isolated by simplify economical process. The % yield was found to be 80% and particle range was 32-65 μm.